Generation of a Retinoblastoma (Rb)1-inducible dominant-negative (DN) mouse model - Tarang, Shikha; Doi, Songila M. S. R.; Gurumurthy, Channabasavaiah B.; Harms, Donald; Quadros, Rolen; Rocha-Sanchez, Sonia M. (Frontiers in Cellular Neuroscience, 2015)
Retinoblastoma 1 (Rb1) is an essential gene regulating cellular proliferation, differentiation, and homeostasis. To exert these functions, Rb1 is recruited and physically interacts with a growing variety of signaling pathways. While Rb1 does not appear to be ubiquitously expressed, its expression has been confirmed in a variety of hematopoietic and neuronal-derived cells, including the inner ear hair cells (HCs). Studies in transgenic mice demonstrate that complete germline or conditional Rb1 deletion leads to abnormal cell proliferation, followed by massive apoptosis; making it difficult to fully address Rb1’s biochemical activities. To overcome these limitations, we developed a tetracycline-inducible TetO-CB-myc6-Rb1 (CBRb) mouse model to achieve transient and inducible dominant-negative (DN) inhibition of the endogenous RB1 protein. Our strategy involved fusing the Rb1 gene to the lysosomal protease pre-procathepsin B (CB), thus allowing for further routing of the DN-CBRb fusion protein and its interacting complexes for proteolytic degradation. Moreover, reversibility of the system is achieved upon suppression of doxycycline (Dox) administration. Preliminary characterization of DN-CBRb mice bred to a ubiquitous rtTA mouse line demonstrated a significant inhibition of the endogenous RB1 protein in the inner ear and in a number of other organs where RB1 is expressed. Examination of the postnatal (P) DN-CBRb mice inner ear at P10 and P28 showed the presence of supernumerary inner HCs (IHCs) in the lower turns of the cochleae, which corresponds to the described expression domain of the endogenous Rb1 gene. Selective and reversible suppression of gene expression is both an experimental tool for defining function and a potential means to medical therapy. Given the limitations associated with Rb1-null mice lethality, this model provides a valuable resource for understanding RB1 activity, relative contribution to HC regeneration and its potential therapeutic application.